Entrepreneurial Marketing and Consumer Need Adaptability for Batik Industry Marketing Performance in Lasem, Rembang - Ahmad Ali (Arthatama: Journal of Business Management and Accounting, 2019)
The purpose of this research is to analyze how entrepreneurial marketing is able to develop business networks and adapt to consumer needs, so that competitive advantage will be achieved which is then expected to be able to improve marketing performance. This study took 120 respondents who owned Lasem batik SMEs in Rembang, Central Java. The analytical tool used is SEM (Structural Equation Modeling). The results of data analysis for the entire model meet the Goodness of Fit criteria with chi square = 89.718, degrees of freedom (df) = 100, probability = 0.760, CMIN/DF = 0.897, GFI = 0.914, AGFI = 0.884, TLI = 1.025, CFI = 1,000 and RMSEA = 0,000. Thus, it can be said that the proposed research model can be accepted. The results of the analysis carried out prove that entrepreneurial marketing can increase consumer need adaptability, competitive advantage and marketing performance.